Effects of Surface in the IR and Raman Spectrum of Porous Silicon Carbide. Issue 1 (May 2020) - Bermeo, R; Arellano, L.; Trejo, A; Salazar, F; Calvino, M.; Miranda, A; Cruz-Irisson, M
Abstract: Porous Silicon carbide has been identified as an attractive material for its use as electrode in supercapacitors, however the theoretical investigations about its properties, specially its vibrational properties, are still scarce. In this work the effect of the Si-C surface ratio on the vibrational properties, IR and Raman spectrum of porous silicon carbide was studied using the first principles density functional perturbation theory. The porous structures were modelled by removing atoms in the [001] direction from an otherwise perfect SiC crystal using the supercell scheme. The morphology of the pores was chosen so there would be more Si or C in the pore surface. The results show that the vibrational properties, and thus the IR and Raman spectrum of the porous SiC change depending if the pore surface is either Si or C rich, having the Si-rich pores more low frequency modes due to its higher mass. Also, the effects of phonon confinement are lessened by the effect of surface passivation, thus indicating that the surface plays an important role in the IR and Raman characterization of these structures.